Bulletin 93 Miners' Nystagmus - Frederick L. Hoffman (The National Institute for Occupational Safety and Health (NIOSH), 1916)
Miners' nystagmus is the result of a peculiar form of eyestrain, which often results in impairment of vision and a consequent diminu- tion of the wage-earning capacity of the workman. Historically it has been pointed out by Shufflebotham that "This disease was first recognized by Gillett, of Sheffield, about 1854, although no case was mentioned in medical literature until 1861, when the symptoms were described by De Conde, a Belgian physician. Cases were reported by Pepp Müller as early as 1860, by Von Graefe in 1873, and by Bell Taylor, of Nottingham, and by Nieden in 1874. In this country (England) we are indebted to a very large extent to the observations and writings of the late Simeon Snell and for his pioneer work on this many-sided disease; in France Dransart occupies a similar position." In the treatise on "The Effects of Arts, Trades, and Professions," by C. Turner Thackrah, published in London in 1832, it is stated that- The complexion of the colliers, even after the removal of the dirt, is generally sallow and unhealthy. Their eyes, from the swelling of the lids, appear small, are affected with chronic inflammation and intolerant of full light. * Sickness and vomiting sometimes affect persons at their commencing the employ; and many, after a few years' trial, are obliged, by the injury which their health has sustained, and especially by the weakness of their eyes, to leave the mine. According to Greer, an authority on industrial diseases and acci- dents, miners' nystagmus occurs in 5 per cent of all miners, but it is quite probable that the reference is to European coal miners rather than to men employed in all branches of the mineral industry. According to the same authority, miners' nystagmus "is associated with a twitching of the eyelids and with considerable diminution of the range of movement of the eyes, and is particularly liable to occur in patients whose vision is subnormal owing to errors of refraction, especially astigmatism. It causes much inconvenience to those suf- fering from it and prevents them from following their usual occupa- tion as, owing to the movements of the eyes, everything at which they look appears to be in a state of perpetual motion, and in conse-